The Wear and Tear on Health: What is the Role of Occupation? - Bastian Ravesteijn; Hans van Kippersluis; Eddy van Doorslaer (Tinbergen Institute, 2013)
While it seems evident that occupations affect health, effect estimates are scarce. We use a job characteristics matrix in order to characterize occupations by their physical and psychosocial burden in German panel data spanning 26 years. Employing a dynamic model to control for factors that simultaneously affect health and selection into occupation, we find that manual work and low job control both have a substantial negative effect on health that increases with age. The effects of late career exposure to high physical demands and low control at work are comparable to health deterioration due to aging by 16 and 23 months respectively.
Keywords: J24; I12; 330; Labor; health; dynamic panel data; Berufsgruppe; Gesundheitsrisiko; Panelforschung; Deutschland